Disruption of ATRX-RNA interactions uncovers roles in ATRX localization and PRC2 function - Wenqing Ren (Nature Portfolio, 2020)
ATRX is an RNA binding protein that mediates targeting of polycomb repressive complex 2 (PRC2) to genomic sites. Here the authors identify the RNA binding region and show that the RNA binding is required for ATRX localization and for its recruitment of PRC2 to a subset of polycomb targets.